2023
DOI: 10.1021/acs.jpclett.2c03572
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of Dichloromethane by a Vacuum Ultraviolet Krypton Lamp: Competition Between Photoinduced Ion-Pair and Photodissociation-Assisted Photoionization

Abstract: The photodissociation and photoionization behaviors of haloalkanes in the VUV regime are important to fully understand the mechanism of ozone depletion in the stratosphere. The ionization of dichloromethane (CH2Cl2) under the irradiation of 10.0 and 10.6 eV light was investigated. CH2Cl+ was observed at 10 Pa, while both CH2Cl+ and CHCl2 + were observed at higher pressure. The production efficiency of CH2Cl+ decreased with the increasing number density of CH2Cl2, while that of CHCl2 + increased. A kinetic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…As shown in Figure a, the TIC almost remained unchanged as the humidity increased, indicating interconversion between ions through ion-molecule reactions. The relation of ion intensities with pressure and reaction time in the ionization source strongly implied that CH 2 Cl + was the primary ion, which was formed through ion-pair or photodissociation-assisted photoionization of CH 2 Cl 2 in the photoionization region . The ion-molecule reactions between CH 2 Cl + and H 2 O resulted in the formation of intermediate product ion CH 2 OH + and their hydrated ions (–) directly or through CX 2 Cl + (H 2 O).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure a, the TIC almost remained unchanged as the humidity increased, indicating interconversion between ions through ion-molecule reactions. The relation of ion intensities with pressure and reaction time in the ionization source strongly implied that CH 2 Cl + was the primary ion, which was formed through ion-pair or photodissociation-assisted photoionization of CH 2 Cl 2 in the photoionization region . The ion-molecule reactions between CH 2 Cl + and H 2 O resulted in the formation of intermediate product ion CH 2 OH + and their hydrated ions (–) directly or through CX 2 Cl + (H 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al found the primary photoionization product ions of CH 2 Cl 2 were CH 2 Cl + and CHCl 2 + at relatively low pressure of 25–150 Pa and proposed the ion-pair or photodissociation-assisted photoionization mechanism. There are several questions to be addressed before we can understand the difference between the two studies.…”
mentioning
confidence: 99%
“…30−33 Radical ions could also result from the photoionization of photodissociation products during chlorinated methanes' VUV photoionization. 34 Sensitivities and LODs of EUV-PI-TOFMS. Figure 4 shows the sensitivity curves of CH 3 Cl (black), CH 2 Cl 2 (red), CHCl 3 (blue), and CCl 4 (green) in a concentration range of 1 to 100 ppbv.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The mass peak at m / z 116 is attributed to unknown matter from synthetic air, speculatively. CH 2 Cl + , CHCl 2 + , and CCl 3 + formations have been observed in the VUV photodissociative photoionization of chlorinated methanes. Radical ions could also result from the photoionization of photodissociation products during chlorinated methanes’ VUV photoionization …”
Section: Resultsmentioning
confidence: 99%
“…At first, researchers improve the light intensity of the VUV beam by developing high-power VUV lamps. , Second, since PI is initiated by collisions between photons and gas analyte molecules, increasing the source pressure can also promote analyte ionization through more frequent photon–molecule collisions. Another way to enhance PI efficiency is to introduce a dopant to the source to induce the dopant-assisted chemical ionization. ,, For this strategy, the dopant molecules absorb the photons and form sufficient reagent ions that can further react with the analyte molecules to induce their ionization. Volatile compounds such as benzene, toluene, hydrogen sulfide, and CH 2 Cl 2 are commonly used dopants. ,, Despite being effective in enhancing ion yields, these solvents are not suitable for widespread use as they may cause some health and environmental issues. Some green dopants such as O 2 have also been developed for PI analysis. The reactive O 2 + ions are first generated as precursor ions and then used to initiate selective analyte ionization .…”
mentioning
confidence: 99%